2018
DOI: 10.3892/ol.2018.9705
|View full text |Cite
|
Sign up to set email alerts
|

AKR1B10 expression predicts response of gastric cancer to neoadjuvant chemotherapy

Abstract: Effective methods for predicting tumor response to preoperative chemotherapy are required. Aldo-ketoreductase family 1 member B10 (AKR1B10) is predominantly expressed in the gastrointestinal tract and serves an important function in cancer development and progression. The present study investigated whether AKR1B10 expression may predict the therapeutic response of locally advanced gastric cancer. A total of 53 patients with gastric cancer underwent neoadjuvant chemotherapy followed by surgery between January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Immunohistochemical analysis has revealed that AKR1B10 is localized in the rapidly renewing epithelial cells of the colon [ 68 ] and stomach [ 69 ]. In contrast, AKR1B10 is markedly decreased or undetectable in cancerous lesions of the colon [ 68 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ] and stomach [ 69 , 77 , 78 , 79 ] ( Table 3 ), as well as in precancerous lesions of the colon (including ulcerative colitis), Crown’s disease, and adenomatous polyps [ 68 , 73 ]. Zu et al [ 73 ] reported that AKR1B10 is critical for protecting host cells from DNA damage induced by electrophilic carbonyl compounds, which are ingested and/or metabolically formed in the intestine.…”
Section: Akr1b10 In the Gastrointestinal Tract And Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical analysis has revealed that AKR1B10 is localized in the rapidly renewing epithelial cells of the colon [ 68 ] and stomach [ 69 ]. In contrast, AKR1B10 is markedly decreased or undetectable in cancerous lesions of the colon [ 68 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ] and stomach [ 69 , 77 , 78 , 79 ] ( Table 3 ), as well as in precancerous lesions of the colon (including ulcerative colitis), Crown’s disease, and adenomatous polyps [ 68 , 73 ]. Zu et al [ 73 ] reported that AKR1B10 is critical for protecting host cells from DNA damage induced by electrophilic carbonyl compounds, which are ingested and/or metabolically formed in the intestine.…”
Section: Akr1b10 In the Gastrointestinal Tract And Cancermentioning
confidence: 99%
“…A poor prognosis in gastric cancer is suggested by the down-regulation of AKR1B10 expression [ 78 ]. By contrast, patients who underwent neoadjuvant chemotherapy showed that high AKR1B10 expression was associated with lymph node metastasis and a poorer prognosis, along with a weak response to neoadjuvant chemotherapy [ 79 ]. In addition, the overexpression of AKR1B10 in gastric cancer MKN46 cells stimulates migration [ 18 ] and down-regulates peroxisome proliferator-activated receptor-γ (PPARγ) that is closely linked to growth suppression and death of cancer cells [ 103 ].…”
Section: Akr1b10 In the Gastrointestinal Tract And Cancermentioning
confidence: 99%
“…After full-text review, 12 articles were excluded. Eventually, we identi ed 11 articles published between 2014 and 2019, which were included in the nal analysis [5][6][7][8][9][10][11][12][13][14][15]. The ow diagram of the literature search is shown in Fig1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Studies have shown that AKR1B10 is characterized by obvious carcinogenicity and can be used as a tumor marker [4]. Recently, an increasing number of studies showed that abnormal expression of AKR1B10 is signi cantly correlated with the prognosis of certain solid tumors [5][6][7][8][9][10][11][12][13][14][15]. However, the currently available results are inconsistent, and the prognostic value of AKR1B10 remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…AKR1B10 typically expresses in the gastrointestinal tract, including human colon, liver, adrenal glands and small intestine. Oppositely, low expression of AKR1B10 has been identified in colon cancer, stomach cancer, head and neck cancer [8,9], while high expression of AKR1B10 has been reported in various solid cancers, such as breast cancer, hepatocellular carcinoma, non-small cell lung carcinoma, cervical, pancreatic carcinoma and endometrial cancers [10][11][12][13][14]. Of note, our tissue microarray results showed that cases with low expression of AKR1B10 are predominant in the early stage of colon cancer, while the percentage of cases with high expression of AKR1B10 are substantially increased in the late stage of colon cancer.…”
Section: Introductionmentioning
confidence: 99%